The ING1a Tumor Suppressor Regulates Endocytosis to Induce Cellular Senescence Via the Rb-E2F Pathway - Rajarajacholan, Uma Karthika (Public Library of Science, 2013)
The INhibitor of Growth (ING) proteins act as type II tumor suppressors and epigenetic regulators, being stoichiometric members of histone acetyltransferase and histone deacetylase complexes. Expression of the alternatively spliced ING1a tumor suppressor increases >10-fold during replicative senescence. ING1a overexpression inhibits growth; induces a large flattened cell morphology and the expression of senescence-associated β-galactosidase; increases Rb, p16, and cyclin D1 levels; and results in the accumulation of senescence-associated heterochromatic foci. Here we identify ING1a-regulated genes and find that ING1a induces the expression of a disproportionate number of genes whose products encode proteins involved in endocytosis. Intersectin 2 (ITSN2) is most affected by ING1a, being rapidly induced >25-fold. Overexpression of ITSN2 independently induces expression of the p16 and p57(KIP2) cyclin-dependent kinase inhibitors, which act to block Rb inactivation, acting as downstream effectors of ING1a. ITSN2 is also induced in normally senescing cells, consistent with elevated levels of ING1a inducing ITSN2 as part of a normal senescence program. Inhibition of endocytosis or altering the stoichiometry of endosome components such as Rab family members similarly induces senescence. Knockdown of ITSN2 also blocks the ability of ING1a to induce a senescent phenotype, confirming that ITSN2 is a major transducer of ING1a-induced senescence signaling. These data identify a pathway by which ING1a induces senescence and indicate that altered endocytosis activates the Rb pathway, subsequently effecting a senescent phenotype.